Long‐term risk of recurrence in patients with a first unprovoked venous thromboembolism managed according to d‐dimer results; A cohort study. (20th May 2019) - Kearon, Clive; Parpia, Sameer; Spencer, Frederick A.; Schulman, Sam; Stevens, Scott M.; Shah, Vinay; Bauer, Kenneth A.; Douketis, James D.; Lentz, Steven R.; Kessler, Craig M.; Connors, Jean M.; Ginsberg, Jeffrey S.; et al.
Abstract: Essentials Long‐term recurrence risk after a first unprovoked VTE with negatived ‐dimer levels is uncertain. Anticoagulation was stopped ifd ‐dimer was negative, and was continued ifd ‐dimer was positive. Five years after stopping anticoagulants, recurrent VTE was 30% in men and 17% in women. Negatived ‐dimers do not justify stopping anticoagulants in most men but appear to in most women. Background: The long‐term risk of recurrence in patients with a first unprovoked venous thromboembolism (VTE) who have negatived ‐dimer results is uncertain. Objectives: To determine this risk, including in subgroups based on sex. Patients and methods: ln a prospective interventional cohort study of 410 patients with a first unprovoked VTE, anticoagulants were stopped ifd ‐dimer was negative on therapy and 1 month after stopping therapy. Other patients remained on anticoagulant therapy. We previously reported findings after a mean of 2.2 years. The current report includes 3 years of additional follow‐up in 293 of these patients. Results: During a median follow‐up of 5.0 years, recurrent VTE after stopping therapy in response to negatived ‐dimer testing was 5.1% (95% confidence interval [CI], 3.6‐6.5) per patient‐year overall, 7.5% (95% CI, 5.5‐10.0) in men, 3.8% (95% CI, 2.0‐6.6) in women with VTE not associated with estrogens, and 0.4% (95% CI, 0.0‐2.3) in women with VTE associated with estrogens ( P < 0.001 for three‐group comparison). Risk of recurrence at 5 years was 21.5% (95% CI, 16.4‐26.5) overall, 29.7% (95% CI, 22.1‐37.3) in men, 17.0% (95% CI, 8.1‐25.9) in non‐estrogen women, and 2.3% (95% CI, 0.0‐6.8) in estrogen women. Conclusion: The long‐term risk of recurrence in patients with a first unprovoked VTE who have negatived ‐dimer results is not low enough to justify stopping anticoagulant therapy in men, but appears to be low enough in women for many to choose stopping therapy (ClinicalTrials.gov; NCT 00720915).